The current status of Cyberbullying research: a short review of the literature. (August 2022) - Vismara, Matteo; Girone, Nicolaja; Conti, Dario; Nicolini, Gregorio; Dell'Osso, Bernardo
Abstract : The present review will provide an up-to-date discussion of the latest in Cyberbullying (CBB) research. First, the conceptualization will be addressed, focusing on existing definitions and assessment tools. Considering the Internet as the medium of CBB, the affinity with other problematic behaviors conducted online is noted and we debated whether to consider CBB as a mental condition. Data on prevalence and people at risk will be reported, picturing the distribution of this phenomenon, but also the limitations of current epidemiological studies. More solid data that investigated the consequences of CBB on the mental health of victims and perpetrators will be discussed. Last, prevention and treatment strategies will be suggested according to literature evidence. Despite the fact that the number of studies on CBB has surged in the last few years, numerous limitations still exist and these will be addressed in the 'Conclusion' section as future research priorities. Highlights: CBB involves the use of digital media platforms with the intent to harass, humiliate, or threaten others. CBB still lacks a universally accepted definition, conceptualization, and assessment tool. Most recent meta-analyses confirmed the association between CBB and negative outcomes. Preventive strategies are rarely evidence-based and treatment approaches are needed.